Association between marginal bone loss and bone quality at dental implant sites based on evidence from cone beam computed tomography and periapical radiographs - Amir Eskandarloo; Reza Arabi; Mohsen Bidgoli; Faezeh Yousefi; Jalal Poorolajal (Wolters Kluwer Medknow Publications, 2019)
Objective: The aim of this study was to assess bone quality in patient's preoperative cone beam computed tomography (CBCT) and their relation with marginal bone loss at implant placement sites over follow-up periods. Materials and Methods: In this retrospective cross-sectional study, 100 implants were evaluated. The implants had been placed in the maxillary and mandibular edentulous areas. Bone quality at implant placement sites was measured on preoperative CBCTs and then classified by two observers according to Lekholm and Zarb classification. Marginal bone height was then measured on periapical radiographs obtained at baseline and then 6, 12, 18, 24, and 30 months' follow-up periods from a reference point (implant shoulder) to the bone-implant interface. The relation between bone quality and bone loss was assessed. ANOVA was used to compare mean difference among groups and Pearson correlation coefficient to assess the correlation between observers. All statistical analyses were performed at 0.05 significance level using Stata 11 software (StataCorp, College Station, TX, USA). Results: Of 100 implants, 48 were placed in the maxilla and 52 in the mandible. There was no significant difference between bone quality and the mean bone loss at follow-up periods. Using Pearson's correlation coefficient, it was shown that with an increase in bone quality, marginal bone loss was decreased at follow-up periods. Conclusions: The results confirmed that during the follow-up periods, less bone loss was observed in implant areas with higher bone quality and CBCT is a reliable tool for assessing bone quality at implant placement sites and estimation of subsequent treatment prognosis.